2017
DOI: 10.1038/s41467-017-02076-0
|View full text |Cite
|
Sign up to set email alerts
|

Roles of two types of heparan sulfate clusters in Wnt distribution and signaling in Xenopus

Abstract: Wnt proteins direct embryonic patterning, but the regulatory basis of their distribution and signal reception remain unclear. Here, we show that endogenous Wnt8 protein is distributed in a graded manner in Xenopus embryo and accumulated on the cell surface in a punctate manner in association with “N-sulfo-rich heparan sulfate (HS),” not with “N-acetyl-rich HS”. These two types of HS are differentially clustered by attaching to different glypicans as core proteins. N-sulfo-rich HS is frequently internalized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(102 citation statements)
references
References 68 publications
6
96
0
Order By: Relevance
“…Due to their hydrophobic nature ( Willert et al, 2003 ), fully processed Wnts are not thought to be capable of freely moving over long distances in the extracellular space on their own ( Langton et al, 2016 ), and it remains to be determined where in the extracellular environment Wnt/EGL-20 spreads and if spreading involves association with cell surface or extracellular matrix proteins ( Han et al, 2005 ; Fuerer et al, 2010 ; Mii et al, 2017 ), structures such as lipoprotein particles ( Neumann et al, 2009 ; Panáková et al, 2005 ) or exosomes/microvesicles ( Korkut et al, 2009 ; Gross et al, 2012 ; Greco et al, 2001 ), and/or other interacting molecules to modulate Wnt solubility ( Mii and Taira, 2009 ; Mulligan et al, 2012 ; Chang and Sun, 2014 ). While we have shown that extracellular dispersal is required for shaping a long-range Wnt gradient, the endogenous factors that promote and/or hinder ligand spreading await further characterization.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their hydrophobic nature ( Willert et al, 2003 ), fully processed Wnts are not thought to be capable of freely moving over long distances in the extracellular space on their own ( Langton et al, 2016 ), and it remains to be determined where in the extracellular environment Wnt/EGL-20 spreads and if spreading involves association with cell surface or extracellular matrix proteins ( Han et al, 2005 ; Fuerer et al, 2010 ; Mii et al, 2017 ), structures such as lipoprotein particles ( Neumann et al, 2009 ; Panáková et al, 2005 ) or exosomes/microvesicles ( Korkut et al, 2009 ; Gross et al, 2012 ; Greco et al, 2001 ), and/or other interacting molecules to modulate Wnt solubility ( Mii and Taira, 2009 ; Mulligan et al, 2012 ; Chang and Sun, 2014 ). While we have shown that extracellular dispersal is required for shaping a long-range Wnt gradient, the endogenous factors that promote and/or hinder ligand spreading await further characterization.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that two different types of heparan sulfate proteoglycans (HSPG), which are separately clustered on the cell membrane, are differently associated with Wnt and sFRP 35 . While one type of the HSPG, which is enriched with N-sulfation on the heparin sulfate chain, is preferentially associated with Wnt8 and involved in the signaling, the other type, which is enriched with N-acetylation, is preferentially associated with Frzb, Xenopus sFRP3, and Wnt8/Frzb complexes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the presence of Wnt, large cluster patches containing LRP6 have been observed (> 200 nm). More recently, evidence from various studies suggests that select proteins, lipids, and even saccharides are involved in the formation of Wnt/β-catenin signaling-associated nanoclusters [14, 111114]. The Wnt/β-catenin signaling pathway positive feedback regulator Ly6 family protein LY6/PLAUR domain-containing 6 (Lypd6) is required for LRP6 phosphorylation and activation in lipid rafts.…”
Section: Dynamic Assembly Of Plasma Membrane Signaling “Hot Spots”mentioning
confidence: 99%
“…Similarly, other plasma membrane components such as heparin sulfate (HS), cholesterol, and phosphatidylinositol-4,5-bisphosphate (PIP 2 ) might also play a role in Wnt/β-catenin pathway-related nanoclustering. Two types of HS molecules, “N-sulfo-rich HS” (N-sulfo HS) and “N-acetyl-rich HS” (N-acetyl HS), have been shown to form distinct 200-nm clusters, as measured by STED microscopy [114]. Interestingly, N-sulfo HS, not N-acetyl-HS, preferably colocalize with the Wnt receptors Fz and LRP6 as well as LRP6’s active counterpart, phosphor-LRP6 [114].…”
Section: Dynamic Assembly Of Plasma Membrane Signaling “Hot Spots”mentioning
confidence: 99%
See 1 more Smart Citation